Reviewing Vietnam's Nationally Determined Contribution: A New Perspective Using the Marginal Cost of Abatement - Escobar Carbonari, Daniel; Grosjean, Godefroy; Läderach, Peter; Nghia, Tran Dai; Sander, Bjoern Ole; McKinley, Justin; Sebastian, Leocadio; Tapasco, Jeimar (Frontiers in Sustainable Food Systems, 2019)
The processes countries use to revise their Nationally Determined Contributions (NDCs) under the UNFCCC's Paris Agreement will be key to ensure that their pledges lead to effective climate change policy. In many developing countries, the agriculture, forestry and other land use (AFOLU) sector is central to their NDCs. For this study, a marginal abatement cost (MAC) curve was used to review Vietnam's mitigation pledges pertaining to the AFOLU sector. We conclude that Vietnam has the potential to increase its NDC pledges, especially in the land use sector and through negative cost mitigation measures including water techniques for rice cultivation, agroforestry, and management of livestock diets and manure. While the MAC curve alone is insufficient to prioritize policy options, this study highlights the fundamental importance of continuous data improvement and refinement for monitoring NDC actions and ultimately achieving the goals set out in the Paris Agreement.